The Effect of the Strategic Vigilance on the Lean Production: A Field Study Conducted on the Jordanian Dairy Company - Al-Qaruty, Tamara Mahmoud Rasheed (International Journal of Membrane Science and Technology, 2023)
This study aimed to demonstrate the effect of the strategic vigilance on the lean production in the Jordanian Dairy Company as a case study. This study dealt with the effect of the strategic vigilance along with its dimensions of (competitive vigilance, social vigilance, commercial vigilance, and technological vigilance) on the lean production in its dimensions of (continuous improvement, empowerment of employees and agility of operations) in the Jordanian Dairy Company (Maha). This study which adopted the descriptive analytical method was applied on the population, which consisted of the Jordanian Dairy Company (Maha). The researcher designed a special questionnaire as an instrument and distributed it to the sample which consisted of (51) respondents who were selected randomly and then retrieved and subjected to the necessary statistical analyses. The study concluded with many results, the most prominent of which is the existence of a statistically significant effect of strategic vigilance with its combined dimensions on lean production. The competitive vigilance had the greatest impact on lean production, while the technological vigilance had the least effect. In light of the results, the study recommended that the company under research should pay better attention and improve its capabilities towards the strategic vigilance and should focus on the technological vigilance because of its impact on improving its productivity and raising its capabilities towards the lean production in the future.